EFEKTIVITAS KOMUNIKASI PERSUASIF GURU DALAM MENINGKATKAN KEPERCAYAAN ORANG TUA MURID (Studi Kasus : MTs Syamsul Ulum Sukabumi) - Ilham Sadjali (Universitas Pahlawan Tuanku Tambusai, 2022)
School is an educational institution that conducts learning for students. A good strategy needs to be pursued so that the school is attractive to parents so that new students at the school will increase. Persuasive communication is certainly one of the techniques in increasing the interest and trust of students and parents to enroll in the school. With the persuasive communication is expected to provide positive information to others. Persuasive communication is communication that affects the audience or communicant, so that they act in accordance with what the communicator expects. This study aims to find out how the effectiveness of persuasive communication built by teachers in increasing the trust of parents of students, as well as knowing how parents believe in persuasive communication carried out by the school. This study uses a qualitative method by conducting documentation, observation and interviews. The results of the study indicate that persuasive communication built by teachers is very influential in creating effective communication in increasing trust in students. Based on information from interviews with teachers and school principals, the researchers concluded that the effectiveness of teachers' persuasive communication in increasing parental confidence in MTs Syamsul ulum runs effectively in accordance with theories and information from interviews with parents. In building trust with parents, teachers of MTs Syamsul Ulum made visits to several elementary schools/madrasah Ibtidaiyah and Islamic boarding schools by distributing brochures, pamphlets and letters as well as promoting excellent programs owned by the school so that parents believe in sending their children to MTs Syamsul Ulum. Keyword: Effectiveness, Persuasive Communication, Increase Trust